THE PSYCHOLOGICAL IMPACT (POSITIVE AND NEGATIVE) AND BEHAVIOURAL CHANGES IN ONLINE LEARNING ON STUDENTS USING FACTOR ANALYSIS - Nur'ainul Miftahul Huda; Nurfitri Imro'ah (Universitas Singaperbangsa Karawang, 2021)
The psychological impact of a pandemic is one focus that cannot be ignored. One of the objects most impacted is students (in this study, it is focused on university students). The covid-19 pandemic has changed everything that could previously be held face-to-face into online learning. Mobility is forced to be reduced; students are asked to be more independent and must be able to adapt quickly to online learning methods. These changes cause many psychological impacts that arise, starting from positive, negative, and behavioural changes. This study provides an overview of the psychological effects of students on learning during the pandemic. The view regarding the gender of students, whether it impacts the psychological impact, is also considered in this study. The most important thing discussed is grouping the psychological effects on students into several factors using factor analysis. The data used is questionnaire data to students who experience learning methods from offline to online learning. The results show consecutively two, three, and four main factors: positive impact, negative impact, and behaviour change.